2003
DOI: 10.1098/rsbl.2003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous, ultraviolet-rich mouth colours in begging chicks

Abstract: There is as yet no clear consensus on the function of vivid mouth colours in begging chicks. A major obstacle to our understanding has been that no studies have measured gape colours independently of human colour perception. Here, we present the first study, to our knowledge, to use UV-VIS spectrometry to quantify the gape colour, background nest colour and nest light environment of eight European passerines. Both mouths and the surrounding flanges show striking and previously unreported peaks of reflectance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 19 publications
4
72
2
1
Order By: Relevance
“…Birds' nests exhibit a wide range of spectral properties that arise from their variable geometry and exposure to solar radiation . Thus, nest light properties may have influenced the evolution of egg and nestling traits used in visual detection by parents (Heeb et al 2003;Hunt et al 2003). In this vein, it has recently been proposed that the importance of ultraviolet (UV) radiation for conspicuousness is particularly highlighted in dark environments such as hole nests because the radiance from the background (nest material and wooden cavity) is considerably lower for the UV light than in open nests Veiga & Polo 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Birds' nests exhibit a wide range of spectral properties that arise from their variable geometry and exposure to solar radiation . Thus, nest light properties may have influenced the evolution of egg and nestling traits used in visual detection by parents (Heeb et al 2003;Hunt et al 2003). In this vein, it has recently been proposed that the importance of ultraviolet (UV) radiation for conspicuousness is particularly highlighted in dark environments such as hole nests because the radiance from the background (nest material and wooden cavity) is considerably lower for the UV light than in open nests Veiga & Polo 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since most birds detect near-UV light, photonic structures in birds reflecting in the UV range have aroused considerable interest in recent years, particularly with regard to their potential biological function (Finger and Burkhardt, 1994). They were first discovered in the plumage of several avian species (Prum et al, 1999b;Hausmann et al, 2003) but have also more recently been reported to be present in other avian tissues, including skin (Prum et al, 1999b;Prum and Torres, 2003), mouth tissue (Hunt et al, 2003), and comb tissue. In a recent preliminary report, we provided evidence for the structural basis of UV reflectance from the King Penguin beak horn (Dresp et al, 2005).…”
mentioning
confidence: 99%
“…Depending on the taxon and the ecological context in terms of environmental light conditions, visual communication in the UV band (300-400 nm) may achieve a prominent role (Tovéè 1995;Briscoe & Chittka 2001;Hunt et al 2003;Avilés et al 2008). In birds, UV colouration of integumentary tissues is considered as a 'structural' chromatic component depending upon the arrangement of collagen arrays in the dermis (Prum & Torres 2003).…”
Section: Introductionmentioning
confidence: 99%